Kinetic study of metal ions adsorption by immobilised chitosan - Pitchay, Thanabalan; Jawad, Ali H.; Johari, Ili Syazana; Sabar, Sumiyyah (UiTM Press, 2021)
Chitosan, a biopolymer produced from crustacean shells, may be used as a sorbent for metal ions removal from industrial wastewaters. This study was carried out to evaluate the efficiency of metal ions removal fromaqueous solutions using immobilised chitosan as an adsorbent in a batch adsorption system. Chitosan was immobilised on glass plates using a simple casting technique. Adsorption experiments were carried out as a function of contact time and initial metal ions concentration. The adsorption efficiency increased with increasing initial metal ions concentration (5 –20 mg L-1) and the observed trend was: Ag2+> Cu2+ > Ni2+> Fe3+> Cd2+> Zn2+.The experimental data were fitted to pseudo-first, pseudo-second-order, intra-particle, and liquid film diffusion kinetic models. The applicability of the pseudo-second-order kinetic model indicated that the adsorption behaviour was ascribed by chemisorption. Further data analysis by the diffusion kinetic models suggested that the adsorption of metal ions was controlled by more than one step:adsorption at the active sites, intra-particle, and liquid film diffusion. Overall, this work has shown the possibility of removing metal ions from water using immobilised chitosan. The use of glass plates as the solid support would facilitate the sorbent recovery during and post-adsorption process.